The chalk box kid - Bulla, Clyde Robert frey50; Allen, Thomas B. 1928- (Thomas Burt) (New York : Scholastic Inc., 1987)
Nine-year-old Gregory's house does not have room for a garden, but he creates a surprising and very different garden in an unusual place.
Braille.
77271
Keywords: Artists -- Fiction; Imagination -- Fiction; Gardens -- Fiction